Depictions of Female Protagonists in Digital Games: A Narrative Analysis of 2013 DICE Award-Winning Digital Games. Issue 8 (December 2018) - Perreault, Mildred F.; Perreault, Gregory Pearson; Jenkins, Joy; Morrison, Ariel
Digital games historically hold a spotty record on gender depictions. The lack of depth in female characters has long been the norm; however, an increasing number of female protagonists are headlining games. This study used narrative theory to examine depictions of four female protagonists in four 2013 Design, Innovate, Communicate, Entertain Award-Winning Digital Games: The Last of Us, Bioshock Infinite, Tomb Raider, and Beyond: Two Souls . Studying these media depictions provides context for how women's stories are recorded in society. Stereotype subversions largely occur within familiar game narratives, and the female protagonists were still largely limited and defined by male figures in the games.